Chest Pain on Exertion After the Takeuchi Repair of Anomalous Origin of the Left Coronary Artery: Right Ventricular Ischemia Due to Severe Pulmonary Outflow Tract Obstruction. (January 2015) - van der Bijl, Pieter; Doruyter, Alexander; Decker, Rik de; Lawrenson, John; Comitis, George; Hewitson, John
Right ventricular (RV) outflow obstruction (in the form of valvar or supravalvular pulmonary stenosis) is a well-known complication of the Takeuchi procedure. We describe a 13-year-old male with exertional chest pain, pulmonary stenosis, RV hypertrophy, and consequent RV ischemia, which was confirmed using stress echocardiography and single-photon emission tomography.